First Report of the occurrence of weevils (Insecta: Coleoptera) in plantations of green tea in Brazil - Suguino, Eduardo; Santos-Cividanes, Terezinha Monteiro Dos; Cividanes, Francisco Jorge [UNESP]; Faria, Ana Maria De; Martins, Adriana Novais (De Gruyter, 2013)
We recorded the occurrence of Compsus sp., Compsus niveus, Platyomus cultricollis, and Rembus auricinctus (Coleoptera: Curculionidae) in tea plantations in the municipality of São Miguel Arcanjo, SP, Brazil. The damage caused by these insects is related mainly to the presence of insect fragments in dried tea leaves, hindering the marketing of the product. This is the first report of the occurrence of weevils in tea crops in Brazil.
Keywords: Camellia sinensis; Compsus niveus; Compsus sp.; Platyomus cultricollis; Rembus auricinctus